The Effect of Service Quality, Facilities and Location on Customer Satisfaction: : A case study in the food industry - Winata, Edi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This research was conducted to see the effect of waiters service quality, facilities and location on customer satisfaction at Mutia Garden Medan Restaurant. By using quantitative descriptive data analysis methods, and the analysis model is multiple linear regression, coefficient determination (R2), simultaneous test (F test), partial test (t test), while the application used to process data is spss 22 this study was conducted. The sampling technique used is simple random sampling, obtained a sample of 125 people as customers of this restaurant. By using questionnaires the authors did for data collection. From the results of data processing, it was found that the variables of service quality, facilities and location had a positive and significant effect on guest satisfaction both simultaneously and partially.